Penerapan Dusun Kawasan Bebas Asap Rokok di Kabupaten Bantul, Yogyakarta - Marsiana Wibowo; Ahmad Ahid Mudayana; Zulfa Mustaghfiroh Khasanah (Jurnal Kesehatan Masyarakat Indonesia, 2022)
Background: Bantul Regency is one of the cities that implement the Smoke-Free Healthy Zone program. Based on the results of PHBS data collection in the community and Riskesdas in 2018, the low coverage of PHBS families was mostly due to smoking behavior in the house. Methods: The type of research used is qualitative with a case study design. Data collection was obtained by conducting in-depth interviews, observations, and visual images. The research subjects were 14 people. Results: The results of research on input indicators show that human resources are not appropriate, funding is adequate, there is no renewal of health promotion media, and there is a written policy. In the process indicators, the results of the socialization of written policies, KSABR messages, KSBAR counseling are obtained, but there is no arrangement of duties and responsibilities on the part of the monitoring team. Meanwhile, the output indicators show that KSBAR has a positive impact on residents, there are warnings for those who violate it but there is no special sanction, and a special smoking area has been provided. Conclusion: the evaluation of KSBAR based on input, process, and output indicators has shown good results although there are still parts that are not in line with expectations, such as human resources that are not yet appropriate, there are no special sanctions for violators, there is no renewal of health promotion media and smoking areas that do not comply with regulations.